ALTERNATIVES TO ATTRACT AND MAINTAIN TEACHERS IN RURAL SCHOOLS IN INDONESIA IN CONTEXT OF STRINGENCY - Soebiantoro Soebiantoro (Universitas Islam Balitar, 2015)
This paper describes problems pertaining teachers assigned in the rural areas in the whole Indonesia are inconvenient to work and leave the sites. This paper argues that salient problems exist in terms of triviality field condition, performance motivation, incentive, and lax of implementation management. Evidently, policy made by the decision makers in upper to the lower level of policy makers contributes ineffective supports of teachers ’ needs and necessities in the sites. The effectiveness of Law on Teacher and Lecturer is problematic stipulated for the teachers problems in rural and remote areas.